Efficacy of management strategies for aromatase inhibitor‐induced arthralgia in breast cancer patients: a systematic review. (30th January 2018) - Nahm, Nicole; Mee, Susie; Marx, Gavin
Abstract: Aromatase inhibitors are the gold standard in the treatment of hormone receptor‐positive breast cancer, but lead to an arthralgia syndrome which is implicated in 13–22% of noncompliance. This is the first systematic review of the efficacy of existing management strategies for this side effect. Eligible studies were retrieved from computer searches of Medline, Cochrane and Embase and the significant intervention groups were identified. The risk of bias of selected studies was evaluated and the relevant data items were extracted, summarized and analyzed. A total of 21 studies were discussed in this review representing 12 different interventions. While several trials had positive findings, the major methodological limitations of the studies meant that no definitive evidence could be found supporting any of the interventions. Future trials are needed which address the methodological problems identified in this review. Exercise holds promise for future research based on its proven benefit in breast cancer.